1982
DOI: 10.1073/pnas.79.17.5210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and chromosomal mapping of a human locus related to the transforming gene of Moloney murine sarcoma virus.

Abstract: Human DNA was analyzed for the presence of sequences homologous to the transforming gene (v-mos) of Moloney murine sarcoma virus. A single 2.5-kilobase pair (kbp) EcoRIgenerated fragment of human DNA was identified by using cloned v-mo8 as probe. This DNA was molecularly cloned in a bacteriophage vector. By heteroduplex and restriction enzyme analyses, this human DNA fragment, designated c-mos (human), contained a 0.65-kbp region ofcontinuous homology with v-mos and was present as a single copy in human DNA. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 31 publications
(16 reference statements)
2
12
0
Order By: Relevance
“…The c-sis gene (simian sarcoma virus) was localized to chromosome 22 (61), the c-fes (Snyder-Theilen strain of feline sarcoma virus) to chromosome 15 (60), and c-myb (avian myeloblastosis virus) to chromosome 6 (62). In addition, in agreement with our results, Prakash et ad have reported that c-mos is on chromosome 8 (63). It is intriguing that each of these chromosomes has been implicated in neoplasia-associated chromosome abnormalities.…”
Section: Resultssupporting
confidence: 90%
“…The c-sis gene (simian sarcoma virus) was localized to chromosome 22 (61), the c-fes (Snyder-Theilen strain of feline sarcoma virus) to chromosome 15 (60), and c-myb (avian myeloblastosis virus) to chromosome 6 (62). In addition, in agreement with our results, Prakash et ad have reported that c-mos is on chromosome 8 (63). It is intriguing that each of these chromosomes has been implicated in neoplasia-associated chromosome abnormalities.…”
Section: Resultssupporting
confidence: 90%
“…Analysis of cells from two Ph'-positive patients has revealed that the breakpoint in chromosome 9 is near c-abl (9 (11), has been mapped by using in situ hybridization to band 8q22, the band involved in the 8;21 translocation (12). Moreover, band 21q22, the site of the breakpoint on the chromosome 21 involved in this translocation, is a region which, when trisomic, leads to the development of Down syndrome, the most common chromosomal cause of mental retardation in humans and a chromosomal disease with an increased risk of leukemia (13 …”
mentioning
confidence: 99%
“…(The human chromosome assignment of each isozyme marker is indicated in brackets.) The isozymes used were: glutathione reductase (GSR) [8]; lactate dehydrogenase A (LDHA) [11]; hexosaminidase A (HEXA) [15]; and soluble superoxide dismutase (SOD1) [21].…”
mentioning
confidence: 99%
“…Recent data on the assignment of c-onc genes to human chromosomes from somatic cell hybridization (11)(12)(13)(14)(15)(16)(17)(18) or in situ molecular hybridization studies (19,20) (18,20). An analogous translocation involving the c-myc and immunoglobulin C, loci occurs in BALB/c plasmacytomas (20,28,29).…”
mentioning
confidence: 99%